Exploring the Role of Malaysian Student’s Intrapreneurial Self-Capital in the Relationship between Satisfaction with Life, Academic Performance, and Flourishing - Chua, Bee Seok; Pan, Lee Ching; Rosnah Ismail (2020)
Intrapreneurial self-capital is the construct coined by Di Fabio as a core of individual resources used to cope with career and life construction challenges. In this study, we used the model of Individual Differences in Evaluating Life Satisfaction (IDELS) to examine the mediating role of intrapreneurial self-capital in the relationship between life satisfaction and flourishing among Malaysian undergraduate students. The Intrapreneurial Self-Capital Scale (ISCS), Satisfaction with Life Scale (SWLS), and Flourishing Scale were administered to 665 undergraduate students from one of the public universities in Kota Kinabalu, Sabah, Malaysia. The results reported a significant direct effect of student satisfaction with life to flourishing. A significant path coefficient was also found from satisfaction with life and student academic performance to intrapreneurial self-concept providing the support that student satisfaction with life and academic performance has a positive effect on their intrapreneurial self-concept. The coefficients from intrapreneurial self-concept to flourishing was also significant. This provides initial support that an intrapreneurial self-concept may have a positive mediating effect on the relationship between satisfaction with life, academic performance, and flourishing. We found that the indirect effects of satisfaction with life and academic performance on flourishing through intrapreneurial self-concept were significant. These results provided further support for the mediating effect of intrapreneurial self-concept. The analysis also that revealed satisfaction with life was significantly and positively related to flourishing. However, the finding showed no significant direct effect of student academic performance on flourishing.